Analysis of DNS Security Threats on campus network. (August 2020) - Sha, Feng; Wei, Ying; Wenzhi, Wu
Abstract: DNS, as the entrance to Internet application access, is the only way for all business access. Normal services must access services through DNS, and malicious programs also need to be connected through DNS. In this paper, we focus on the analysis of campus network egress data using traffic analysis technology. And we pay attention to DNS-related data, hoping to find useful information about network attack. Since we collected data for about a month (mainly data about DNS data), we found many attacks and a large number of computer viruses. They are hidden in the normal data stream, but can be recognized by DNS data.